Effect of torrefaction temperature on the elemental composition of bamboo biomass - Carla Goncalves De Oliveira Sarmento; Rosalam Sarbatly; Emma Suali; Muhammad Yusuf Suleiman; Paulo Debiagi (IOP Publishing Ltd., 2025)
Malaysia’s commitment to achieving 70% renewable energy capacity by 2050 under the National Energy Transition Roadmap (NETR) necessitates exploration of sustainable biomass sources. Gigantochloa levis bamboo, known for its rapid growth and high yield, is a promising candidate but suffers from high moisture content and low energy density, limiting its direct use as a solid biofuel. This study investigates the effects of torrefaction at 220–300 °C on the physicochemical and fuel properties of G. levis. Results demonstrate that torrefaction significantly improves fuel quality by increasing carbon content (from 45.6% to 67.9%) and decreasing oxygen content, which enhances the atomic O/C ratio and chemical stability. The higher heating value (HHV) increased by 73%, reaching 25.80 MJ/kg at 300 °C, indicating a substantial enhancement in energy density. Thermogravimetric analysis (TGA) of raw bamboo revealed distinct pyrolysis stages, providing baseline thermal degradation data. These improvements highlight torrefaction as an effective thermochemical pretreatment to advance G. levis as a viable solid biofuel for biomass power generation. Future work will integrate TGA and combustion analyses of torrefied samples and conduct technoeconomic evaluations to assess scalability and practical implementation for large-scale bioenergy applications in Malaysia.